EXAMINING DIGITAL ENTREPRENEURIAL INTENTION FROM VARIOUS THEORIES - Permana, I Putu Hendika; Sumariani, Ni Putu Ayu; Marini, Putu Lidia (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Indonesia faces the challenge of a low number of entrepreneurs which has implications for economic growth and global competitiveness. One strategic solution to overcome this is the development of digital entrepreneurship considering the rapid digital transformation in various sectors. Efforts to increase digital entrepreneurship in Indonesia require a deep understanding of the factors that influence digital entrepreneurial intentions. This study aims to identify the theoretical basis and see the factors in it that support digital entrepreneurial intentions. This study was conducted using an explorative method by searching for previous empirical research in reputable international journals. Various theories were found such as Theory of Planned Behavior, Self-Determination Theory, Technology Acceptance Model, Social Cognitive Theory, Social Cognitive Career Theory, Entrepreneurial Event Model. The results of the study are expected to contribute to further researchers to be able to test digital entrepreneurial intentions so that they can support the growth of digital entrepreneurship in Indonesia.